An evaluation of measurement model for medical tourism research: The confirmatory factor analysis approach (Article) - Zainudin, Awang; Mahadzirah, Mohamad; Asyraf, Afthanorhan (Inderscience Publishers, 2015)
Medical tourism has become one of the most important sectors generating foreign exchange for Malaysia. The government has intensified its effort to promote the country as a popular destination among foreign travellers seeking medical care outside their country. Thus, rigorous research is expected in this particular field. In line with that, this study intends to validate the measurement model for medical tourism research. The mixed method study begins with qualitative approach and ends-up with the quantitative analysis. The medical tourism constructs involved are human capital, physical infrastructure, and patient satisfaction. In the qualitative phase, personal and focus group interviews were conducted to generate items for the respective constructs. The confirmatory factor analysis (CFA) has validated the measurement model of human capital, physical infrastructure, and patient satisfaction for unidimensionality, validity and reliability. Therefore, these measurement models can be assessed for the future research improvements.